2017
DOI: 10.14499/indonesianjcanchemoprev7iss3pp99-103
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Mushroom (Pleurotus ostreatus) Inhibits Migration and Metastasis on 4T1 Breast Cancer Cells

Abstract: Metastasis is the main cause of death among brast cancer patient. Pleorotus ostreatus is known as anticancer agent that inhibits angiogenesis. Ethanolic extract of Pleorotus ostreatus (EEP) which contains lovastatin is predicted to inhibit metastatic cancer through inhibition of MMP-2 and MMP-9. The aim of this study was to determined antiproliferative and anti metastatic activity of EEPw (Ethanolic extract of wet Pleorotus ostreatus) and EEPd (Ethanolic extract of dried Pleorotus ostreatus) in 4T1 metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The assay for determining MMP was an independent prognostic factor. In line with this, the PO ethanolic extract reduced the expression of MMP-9, and molecular docking analysis showed that lovastatin, the compound identified from the extract, showed enhanced binding with either MMP-2 or MMP-9 [28]. Furthermore, the polysaccharide extract PO exhibited a potent reduction in the secretion of MMP-2 and 9 that indicates a reduction in colon cancer cell invasion [3].…”
Section: Gelatin Zymographymentioning
confidence: 61%
“…The assay for determining MMP was an independent prognostic factor. In line with this, the PO ethanolic extract reduced the expression of MMP-9, and molecular docking analysis showed that lovastatin, the compound identified from the extract, showed enhanced binding with either MMP-2 or MMP-9 [28]. Furthermore, the polysaccharide extract PO exhibited a potent reduction in the secretion of MMP-2 and 9 that indicates a reduction in colon cancer cell invasion [3].…”
Section: Gelatin Zymographymentioning
confidence: 61%